Effects of universal vs bedside leukoreductions on the alloimmunization to platelets and the platelet transfusion refractoriness. Issue 1 (February 2015) - Mishima, Yuko; Tsuno, Nelson H.; Matsuhashi, Mika; Yoshizato, Tetsuichi; Sato, Tomohiko; Ikeda, Toshiyuki; Watanabe-Okochi, Naoko; Nagura, Yutaka; Sone, Shinji; Kurokawa, Mineo; Okazaki, Hitoshi
Abstract Background Multiple platelet exposure induces anti-HLA and/or anti-HPA antibody production, which may cause platelet transfusion refractoriness (PTR). In Japan, the universal pre-storage leukocyte reduction (ULR) was fully implemented since 2006, but prior to ULR, in our institution, leukocyte reduction filters were routinely used at the bedside (bedside leukoreduction, BSLR) for all onco-hematological patients receiving multiple platelet transfusions. Objective We retrospectively compared patients receiving platelet transfusions in the era of ULR with those of BSLR era. Materials and methods Patients of the BSLR group (409 cases) and the ULR group (586 cases) were compared in terms of alloimmunization and immunological PTR. The clinico-pathological features, including gender, history of pregnancy, number of exposed transfusion donors, periods of transfusion, and prior stem cell transplantation were compared, and the risk factors of alloimmunization were determined. Results The antibody detection rate was significantly higher in the ULR compared to BSLR group (8.7% vs. 5.4%), as well as the immunological PTR rate (7.3% vs. 3.2%). By the multivariate analysis, female gender and the number of platelet donor exposure, but not universal leukoreduction or transfusion period, were found to be the risk factors strongly associated with alloantibody formation. Conclusion Although ULR may be superior to BSLR in terms of preventing non-hemolytic transfusion reactions, BSLR was found to be as effective as ULR in terms of preventing platelet alloimmunization and refractoriness. Thus, BSLR should be actively indicated as a realistic alternative in developing countries, before the universal leukoreduction is fully implemented.